DNA vs. Mirror‐Image DNA: A Universal Approach to Tune the Absolute Configuration in DNA‐Based Asymmetric Catalysis1. Issue 44 (12th September 2013) - Wang, Jocelyn; Benedetti, Erica; Bethge, Lucas; Vonhoff, Stefan; Klussmann, Sven; Vasseur, Jean‐Jacques; Cossy, Janine; Smietana, Michael; Arseniyadis, Stellios
<x xml:space="preserve">Abstract</x> Mirror mirror on the wall: By taking advantage of the unique structural features of L‐DNA, the first examples of left‐helical enantioselective induction in the field of DNA‐based asymmetric catalysis were realized. Most importantly, this approach is the only one that allows a reliable and predictable access to both enantiomers for any given reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>